decifra-me ou te devoro: Uma análise das variáveis e fatores que influenciam o impacto da pesquisa científica desenvolvida na área de sustentabilidade no Brasil - Jabbour, Charbel José Chiappetta [UNESP]; Jabbour, Ana Beatriz Lopes de Sousa [UNESP]; de Oliveira, Jorge Henrique Caldeira (FapUNIFESP (SciELO), 2013)
The goal of this research is to analyze what are the key variables and factors that, in the perception of researchers in the field of sustainability in Brazil, may be influencing the impact research conducted by them. Therefore, we designed a data collection instrument with 14 variables, responded online by 89 researchers in the field of sustainability in Brazil. The results show that these researchers realize the impact of their research as a process influenced by four factors.
decipher me or i'll devour you: An analysis of the variables and factors that influence the impact of scientific research developed in the area of sustainability in Brazil
Keywords: Exploratory factor analysis; Impact research; Scientometrics; The area of sustainability